THE ADDITIONAL FUNCTIONS OF PORCH AND VAULT IN PANTAI BAHARI FISHING VILLAGE - Nurul Nadjmi; Fadhillah Khairani Asrul (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2018)
Pantai Bahari is one of the fishing villages in Bangkala Subdistrict, Jeneponto Regency, South Sulawesi Province, located in a coastal region where the community works as fishermen. The residents are still tightly holding their belief and respecting their customs, namely by living in traditional indigenous Bugis Makassar stilt house, with its philosophy of portraying the Underworld, the Middle world, and the Upper world over. The people also make some improvements over their house; one of them is against the function of porch and the space under the house (vault) that are perceived to depict ‘the Underworld’. There are some factors influencing the emergence of additional functions of the porch and the vault. A single case study method was employed in this research involving Pantai Bahari fishing village. To analyse the data, both qualitative and quantitative methods were used. The results show several factors causing the additional functions of porch and vault, and the family structure, economic needs, the lack of areas to accommodate events, and the needs for mobility.